Developing Recommendations On The Technical Condition Of "KomiKasaba" Channel And Its Improvement. - Ergashev Khurshid Erkin oglu (Genius Publishing Group, 2023)
In this article, some information is given about the function of hydroelectric units and, at the same time, the importance of water distribution structures in water management, the role of hydroelectric units in distributing the water limit of hydrostations
Keywords: hydronozzle; hydropost; water distribution; limit